Synthesis and characterization of a novel long‐alkyl‐chain ester‐substituted benzimidazole gelator and its octan‐1‐ol solvate. Issue 4 (1st April 2017) - Geiger, H. Cristina; Zick, Patricia L.; Roberts, William R.; Geiger, David K.
Abstract : The synthesis, gelation and aggregation properties of methyl 8‐[4‐(1 H ‐benzimidazol‐2‐yl)phenoxy]octanoate and the crystal structure of its octan‐1‐ol solvate are reported. A four‐molecule hydrogen‐bonded motif consisting of two benzimidazole molecules and two octan‐1‐ol molecules is observed in the solid state. Abstract : The synthesis of a novel benzimidazole derivative with a long‐chain‐ester substituent, namely methyl 8‐[4‐(1 H ‐benzimidazol‐2‐yl)phenoxy]octanoate, (3), is reported. Ester (3) shows evidence of aggregation in solution and weak gelation ability with toluene. The octan‐1‐ol solvate, methyl 8‐[4‐(1 H ‐benzimidazol‐2‐yl)phenoxy]octanoate octan‐1‐ol monosolvate, C22 H26 N2 O3 ·C8 H18 O, (4), exhibits a four‐molecule hydrogen‐bonded motif in the solid state, with N—H…O hydrogen bonds between benzimidazole molecules and O—H…N hydrogen bonds between the octan‐1‐ol solvent molecules and the benzimidazole unit. The alkyl chains of the ester and the octan‐1‐ol molecules are in unfolded conformations. The phenylene ring is canted by 10.27 (6)° from the plane of the benzimidazole ring system. H…C contacts make up 20.7% of the Hirshfeld surface coverage. Weak C—H…π interactions involving the benzimidazole alkyl chain and three aromatic rings are observed.